Tourism and Everyday Livelihood Negotiations: A Case Study of Coastal Fishing Communities in Sulawesi - Hatidja, St; Sulana, Bayu Arif (Advances in Tourism Studies, 2025)
This study investigates how coastal fishing communities in Sulawesi negotiate everyday livelihoods amid the growth of tourism. While tourism has been promoted as a diversification strategy for small-scale fishing economies, little is known about how local households experience and interpret the interplay between traditional livelihoods and emerging tourism opportunities. Adopting a qualitative case study approach, this research draws on interviews, focus groups, and participant observation conducted in two coastal villages in South Sulawesi during 2024. The findings reveal a complex process of negotiation in which fishing families simultaneously embrace, resist, and adapt to tourism. On one hand, tourism creates new income streams through homestays, boat tours, and seafood sales, enabling some households to reduce dependence on uncertain fishing yields. On the other hand, it generates tensions related to resource competition, cultural commodification, and unequal access to benefits. Importantly, the study highlights the ways in which households navigate these changes through flexible livelihood strategies, gendered role adjustments, and community-based norms of sharing. The research contributes to tourism and development scholarship by foregrounding the lived experiences of fishing communities, offering insights into how tourism intersects with traditional economies in Indonesia’s coastal regions.